Built environment correlates of physical activity and sedentary behaviour in older adults: A comparative review between high and low-middle income countries. (May 2019) - Cleland, Claire; Reis, Rodrigo Siqueira; Ferreira Hino, Adriano Akira; Hunter, Ruth; Fermino, Rogério César; Koller de Paiva, Hermes; Czestschuk, Bruno; Ellis, Geraint
Highlights: Different built environment attributes are associated with physical activity in high- and low-middle income countries. Walkability and land use mix were positive and population density negative for physical activity in high-income countries. Access to recreation and neighbourhood characteristics were positive for physical activity in low-middle income countries. Research should focus on advancing the evidence base for built environment attributes and sedentary behaviour. Built environment attributes need to be considered in future research, policy and practice within a complex system.